Gambaran Kualitas Mikrobiologi Es Batu Kristal Dan Es Batu Balok Pada Minuman Di Pujasera Daerah Stasiun Kereta Api Duren Kalibata - Rizka, Devriola Betty Gayu; Rahayu, Cahyawati; Kristianingsih, Yuli (Universitas Mohammad Husni Thamrin, 2024)
Waterborne diseases are infectious diseases that are directly caused by water. An example of a common disease is caused by the bacterium Escherichia coli. Diarrhea can be transmitted through drinking water contaminated with Escherichia coli. Water is one of the sources of life for needs and for consumption (drinking), one of the water used is in the form of ice cubes. Ice cubes have a variety of benefits, one of the benefits is as a complement that is served along with drinks, the addition of ice cubes in drinks is to cause a cold and fresh sensation. Many beverage traders use block ice cubes that are not for their designation. Ice cubes for consumption must be safe from coliform bacteria and Escherichia coli in accordance with the quality standards of PERMENKES NO.2 of 2023. The purpose of this study was to obtain a description of the number of coliform bacteria and Escherichia coli in crystal ice cubes and block ice cubes used by beverage sellers in the Pujasera area of Duren Kalibata Railway Station. This study uses an exploratory descriptive method. The population of this study were beverage sellers who used crystal ice cubes as many as 10 people and ice cubes as many as 8 people in the Duren Kalibata Railway Station Area Food Court with a sample of 8 people each and 8 crystal ice cubes and 8 crystal ice cubes. The results showed that all samples of crystal ice cubes and block ice cubes were positive for Coliform Bacteria, 60% of block ice cubes were positive for Escherichia coli, while 80% of crystal ice cubes were positive for Escherichia coli. This is due to the lack of knowledge, attitudes and actions of traders about the quality of ice cubes that must be maintained. It can be concluded that crystal ice cubes and block ice cubes sold at the Duren Kalibata Railway Station Area Food Court do not meet the requirements of Environmental Quality Standards. For traders and the public to pay attention to the hygienic quality of snacks or drinks that are sold and consumed. Keywords : Block ice cubes, Crystal ice cubes, Beverages, Microbiological Quality